AREAL PARADIGM OF TERRITORIAL IDENTITY: FOUNDATIONS, LIMITS, BEYOND LIMITS - Kagansky, V.L. (Perm Federal Research Centre Journal, 2015)
The study uses, sometimes develops and refines the general approach, methods and results of the following authors: Armand A.D. (the idea of the landscape); Sauer, K. (cultural landscape), Kordonsky S.G (the nonexistence of society in the western sense on the territory of the Russian Federation); Kostinsky G.D. (types of spaces); Krylov M.P. (territorial identity as such and territorial identity of Russia); Plyusnin, Y.M. (distributed lifestyle); Rodoman B.B. (theoretical geography and cultural landscape, network space); Semenov-Tian-Shansky V.P. (landscape); Smirnyagin L.V. (territorial identity), Schreider Y.A. (the notion of systems, types of relations). The article is written from the viewpoint of theoretical geography line Semenov-Tyan-Shansky-Rodoman and uses its tools. Considered grounds and presupposition judgments about spatial identity. Analyzed the prevailing ideas about such identity as areal. Identified types of spatial identity is not reducible to areal. Introduced the idea of monoidentate and polyidentate territory. First considered a number of new types of identities corresponding to the modern cultural landscape, which has network space form and the disposition of social groups in it. Introduced the idea of linear, edge and network spatial identity. All considered and referred to specific geographical situation based - among other things - on their own field research.